An investigation of space and space-time clustering in a large sample of infants with neural tube defects born in Cardiff. Issue 3 (September 1975) - Roberts, C J; Laurence, K M; Lloyd, S
Abstract : Altogether 406 infants with neural tube defects born in Cardiff between 1956-71 were investigated for evidence of space-time clustering and 100 similarly affected infants, together with matched controls born in Cardiff between 1964-66 were investigated for evidence of spatial clustering. No evidence of excessive prevalence in either dimension was observed.